Eksplorasi Matematika pada Kain Tenun Khas Sumba di Rumah Budaya - Momo, Christina A. Ninda; Ina, Yunita Astuti Noberta; Lede, Yulius Keremata (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to identify the types of motifs on woven fabrics originating from the Southwest Sumba region at the Cultural House. This research was conducted through observation and documentation of traditional Sumba woven fabrics available at the Cultural House. Documentation was carried out to obtain several real photos of Sumba woven fabrics at the Cultural House using qualitative research with an exploratory-descriptive approach. Data collection techniques included interviews, observation, and documentation, while data analysis techniques included data reduction, data presentation, and drawing conclusions. The elements contained are geometric patterns. Many motifs are composed of geometric patterns such as straight lines, parallel lines, diamond shapes, and triangles. Sumba woven fabrics are known for motifs rich in philosophical meaning and also containing mathematical elements. These concepts are mainly related to the geometry of flat planes. In Sumba woven cloth, there are patterns called the main pattern and the border pattern. The main pattern is the primary motif that becomes the focus and attention of the weaving being created. The main pattern usually has a larger, more complex design and contains more twists than the other patterns. In addition, there is also the border pattern, which is a motif that frames, surrounds, or sets boundaries for the main pattern. The size and complexity of the border pattern are usually smaller and simpler compared to the main pattern. The border pattern typically consists of lines, dots, or simple geometric shapes.